Perbandingan Efektivitas Antibakteri Ekstrak Daun Kelor (Moringa oleifera) terhadap Pertumbuhan Bakteri Enterococcus faecalis dan Streptococcus mutans Secara in Vitro) - Firdha Muharraran; Suci Erawati; Dini Arta Lestari Dalimunthe (Jurnal Penelitian Pendidikan IPA, 2023)
Streptococcus mutans and Enterococcus faecalis are bacterial pathogens of dental caries and root canal treatment failure. The growth of bacteria that cause dental and oral disease can be inhibited by using antibacterials derived from plants that have antibacterial properties. The aim of the research was to compare the antibacterial effectiveness of Moringa oleifera leaf extract against the growth of Enterococcus faecalis and Streptococcus mutans bacteria in vitro. This type of research is a laboratory experiment with a post test only control group design. The research samples were pure cultures of Streptococcus mutans and Enterococcus faecalis. There were seven treatment groups, namely Moringa leaf extract concentrations of 50%, 25%, 12.5%, 6.25%, 3.125%, positive control chlorhexidine and negative control DMSO with four repetitions each. Testing the antibacterial effectiveness of Moringa leaf extract used the diffusion and dilution method, then the data was analyzed using one way ANOVA and post hoc LSD statistical tests. Based on the research results, it was stated that there was effective inhibitory and killing power of Moringa oleifera leaf extract on the growth of Enterococcus faecalis and Streptococcus mutans bacteria. From the research results, it can be concluded that Moringa oleifera leaf extract is more effective as an antibacterial against Streptoccus mutans compared to Enterococcus faecalis